(untitled) (EAAE Annual Conference Proceedings, 2023)
The paradigms of the past are being questioned. We now have a desire for rebirth, we aspire for a new vision of the world, and the time has come for the architect to equip himself with his most valuable and unique qualities – the ability to provide a vision of a new world and to convey hope. Today, the proximity between the architect and society is remembered and the academy has been called to participate in this innovative process.